Neoadjuvant chemoradiation and surgical excision versus definitive radiotherapy for locally advanced cervix uteri carcinoma: in terms of early and late complications and locoregional recurrence - Hisham Khalifa; Mohamed Ayaty; Reham Oreaba; Reem Emad; Mohamed Salama; khaled Elsebahy; Wael A. Wahab Ghoniem (Journal of the Egyptian National Cancer Institute)
Abstract Objectives Following external beam radiation therapy (EBRT) with concurrent chemotherapy, we analyzed the benefits of surgical resection for locally advanced cervical carcinoma in terms of the frequency and severity of complications and disease-free survival, including cases of adjuvant hysterectomy after failure of resolution post-brachytherapy. Patient and methods Retrospective analysis was utilized to determine the eligibility of 145 cases treated at the National Cancer Institute between January 2015 and June 2021. Of those, 17 patients did not match the requirements, and 8 patients declined to take part in the study. Depending on the major treatment technique, 120 FIGO stage IB3–FIGO stage IVA cervical cancer patients were split into two equal groups of 60 patients each. Sixty patients (50%) received neo-adjuvant EBRT and concurrent platinum-based chemotherapy followed by hysterectomy (group A) and 60 (50%) received definitive radiotherapy only (group B). Results The age at diagnosis of patients was similar, with a mean of 52.5 (range 34–77) and 53.4 (range 25 81) years in group A and group B, respectively (P = 0.675). Majority of the cases in both groups were pathologically squamous cell carcinomas (88.3% in group A and 83.3% in group B) and of grade II differentiation (73.7% in group A and 71.2% in group B). Majority of cases in both groups being FIGO stage II (45% in group A and 40% in group B) and FIGO stage III (40% in group A and 43.3% in group B). Only 17 patients (28.3%) in group A had postoperative complications, while 37 patients (61.7%) in group B suffered from post-treatment complications (P value < 0.001). In group B, 14 patients (23.3%) failed to show complete remission of the disease after completion of treatment, with a mean residual disease of 4.3 cm in diameter (range 2–6 cm), either local or nodal. Salvage hysterectomy post-definitive radiotherapy was done for 8 patients with residual disease (13.3%). In group A, 48 patients had no recurrence during follow-up (80%), while 11 of the patients had either locoregional or metastatic recurrences, or both (18.3%). DFS was comparable between both groups (P = 0.493), excluding 23.3% of group B where failure of complete remission of the disease after completion of treatment barred the patients from the disease-free calculations. The 1-year DFS was 88.1% in group A and 82.6% in group B, while the 3-year DFS was 74.1% in group A and 70.1% in group B. Conclusion There was no difference in disease-free survival or the incidence of locoregional and metastatic recurrence between patients with cervical cancer who had surgery and those who received brachytherapy following EBRT and concomitant chemotherapy. In almost 50% of cases, the surgical patients showed full pathological recovery.